2020
DOI: 10.1039/d0sc01039a
|View full text |Cite
|
Sign up to set email alerts
|

Surface passivation extends single and biexciton lifetimes of InP quantum dots

Abstract: Combined optical spectroscopic study now reveals the photophysical changes of InP QDs upon surface passivation by various methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(116 citation statements)
references
References 62 publications
9
107
0
Order By: Relevance
“…15 Despite these studies, it has only been very recently that a TA study of InP nanocrystals has reported biexciton lifetimes for assynthesized and ZnS shell-passivated InP QDs. 16 The powerdependent bleach recovery kinetics indicate that surface passivation greatly increases the biexciton lifetimes. Passivation is provided by deposition of a very thin ZnS shell and is only partial; PL QYs of 35−40% are obtained.…”
Section: ■ Introductionmentioning
confidence: 99%
“…15 Despite these studies, it has only been very recently that a TA study of InP nanocrystals has reported biexciton lifetimes for assynthesized and ZnS shell-passivated InP QDs. 16 The powerdependent bleach recovery kinetics indicate that surface passivation greatly increases the biexciton lifetimes. Passivation is provided by deposition of a very thin ZnS shell and is only partial; PL QYs of 35−40% are obtained.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Multiexcitonic states in colloidal quantum dots are usually studied by time-resolved photoluminescence and transient absorption spectroscopy. ,− These techniques enable one to measure, for example, the energies and dynamics of biexciton states. There are also some drawbacks, however.…”
mentioning
confidence: 99%
“…Considering the significant deviation from the power law dependence between the fast decay time (<10 ps) and the effective exciton radius (τ ∝ r n ) [ 39 ] in Figure S14, Supporting Information, we attribute the picosecond dynamics to the Auger‐assisted trapping dynamics. [ 40–43 ] The fast trapping terms in the decay profiles of a series of InP/ZnSe/ZnS QDs increased from 2.8 to 10 ps upon increasing the thickness of the ZnSe shell. While the trapping rates are inversely proportional to the ZnSe shell thickness, the energy difference Δ E between two bleaching bands (480–520 nm) in the DA spectra, assigned as band‐edge and trap states, becomes larger (Table 1).…”
Section: Resultsmentioning
confidence: 99%